The Prudential Regulation: the Preventive Effort against Non-Performing Loan (NPL) for MSMEs in Indonesia - Idris, Miftah; Paserangi, Hasbir; Liman, Padma D.; Deviany, Oky (Journal of Ecohumanism, 2025)
This study aims to develop a regulatory framework for the prudential principles to prevent non-performing loans (NPL) in the distribution of bank credit to Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research focuses on Conventional Banks (Mandiri, BNI, BRI, and BPR) in Indonesia, involving interviews with 50 MSME actors who are currently applying for or have previously applied for credit, as well as an analysis of regulations issued by the Financial Services Authority (OJK) and banking data from OJK from 2018 to 2024. The study period is divided into three phases: the Pre-Covid 19 Pandemic Phase (2018–2019), the Covid 19 Pandemic Phase (2020–2021), and the Post-Covid 19 Pandemic Phase (2022–2024). The analysis explores the influence and relationship of these phases with NPL trends, focusing on banks as creditors and MSMEs as debtors. Utilizing Legal Protection Theory, the study emphasizes preventive measures to mitigate the risk of NPL rather than addressing their resolution. The findings highlight the necessity for internal oversight by banks on MSMEs’ credit management and propose that credit agreements include not only collateral from debtors but also insurance mechanisms to secure the credit distributed to MSMEs.